Pharmaceutical assistance within the SUS: the experience of students in Rural Internship from a Pharmacy Course - Luciana Tarbes Mattana Saturnino; Zélia Profeta Luz; Edson Perini; Celina Maria Modena (Universidade de São Paulo, 2009)
The 2002 Brazilian Curricular Lines established a new curriculum for Pharmacy Programs, including amplified information about the Unified Health System (SUS). Following this, some Colleges have implemented a Rural Internship (RI) discipline, as a way to promote: a) adequate information on the SUS, and b) students' interaction with pharmaceutical assistance. In this study we analyzed the perceptions of students enrolled in the Rural Internship program of the undergraduate Pharmacy Program at the Federal University of Minas Gerais. Eight students participated in this study and their perceptions and ideas were obtained by focus groups, both before and after the RI. This information was analyzed by content analysis. The students had a fragmented, distorted view on assistance, before as well as after taking the RI. Nevertheless, the RI provided students with a view of the professional realities and difficulties routinely faced by pharmacists in the public health system. The RI course of the Pharmacy Programs was viewed as an opportunity to improve the professional work within the SUS. As Diretrizes Curriculares de 2002 implantaram um novo currículo para o Curso de Farmácia, trazendo como propósito a aprendizagem para o Sistema Único de Saúde (SUS). Para atender a esta demanda, algumas Faculdades têm implantado a disciplina de Internato Rural (IR) como forma de viabilizar o ensino para o SUS e a interação do aluno com a assistência farmacêutica. Este trabalho analisa a concepção de alunos do IR do Curso de Farmácia da Universidade Federal de Minas Gerais sobre a assistência farmacêutica e sobre a atividade do profissional farmacêutico no SUS. A coleta das informações foi realizada por meio da técnica do grupo focal antes e após o IR. Para a análise dos discursos foi utilizada a técnica da análise de conteúdo. Participaram do estudo oito estudantes. Observou-se que os alunos apresentavam uma visão fragmentada sobre a assistência, tanto antes como após o internato. O IR proporcionou aos estudantes uma visão da realidade e o reconhecimento das dificuldades que o profissional ainda enfrenta nos serviços. Além disso, notou-se que a disciplina de internato no curso de farmácia pode ser uma alternativa que contribui para a atuação e a formação do farmacêutico para o SUS.